1995
DOI: 10.3171/jns.1995.83.1.0067
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade astrocytoma with neuraxis dissemination at diagnosis

Abstract: Little is known about low-grade astrocytoma with neuraxis dissemination at diagnosis. A review of medical records identified this phenomenon in eight of 150 pediatric patients evaluated between 1985 and 1994 for histologically confirmed low-grade astrocytoma. These patients (five male and three female) ranged in age from 5 months to 20 years (median 8 years). Symptoms of neuraxis disease were minimal or absent. Primary tumor sites were the hypothalamus in four cases, brainstem/spinal cord in three, and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
76
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 21 publications
(11 reference statements)
4
76
1
Order By: Relevance
“…This is not, however, the only important factor. Tumor cells are able of crossing piamater and invade CSF pathways; their degree of adhesiveness, their metabolic capacities (adhesion molecule production, protease secretion and growth factor pathway activation) and their antigenic factors also may aid leptomeningeal spread 1,2,3,5,27 . A study with CD44 suggests that this adhesion molecule may play a role in astrocytic invasion and adherence 31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not, however, the only important factor. Tumor cells are able of crossing piamater and invade CSF pathways; their degree of adhesiveness, their metabolic capacities (adhesion molecule production, protease secretion and growth factor pathway activation) and their antigenic factors also may aid leptomeningeal spread 1,2,3,5,27 . A study with CD44 suggests that this adhesion molecule may play a role in astrocytic invasion and adherence 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Leptomeningeal dissemination (LD) of primary central nervous system (CNS) tumors in children has been reported mainly in ependymomas, germ-cell tumors, primitive neuroectodermal tumors, high grade gliomas [2][3][4][5][6][7][8][9] . Low grade gliomas dissemination has been documented in few cases 1,2,5,6,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When intramedullary low-grade astrocytomas metastasize intracranially, most of them have malignant transformation 6,19) . In most of the cases reported up until now, spinal cord tumors that spread intracranially had previous malignant transformation or were high-grade gliomas 7,21,24,25) , even though in children, some cases without malignant transformation have been reported 1,2,5,9,11,17) . In 1995, Claus et al 6) reported the case of a 43-year-old man with intracranial dissemination of a WHO Grade I pilocytic astrocytoma of the cauda equina.…”
Section: Discussionmentioning
confidence: 99%